1999
DOI: 10.1111/j.1530-0277.1999.tb04540.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Beating Rate of Cultured Chick Cardiac Myocytes by Ethanol and Inhibition of the Increase by Antiarrhythmic Drugs

Abstract: Drinking alcohol sometimes causes cardiac arrhythmia, but the precise mechanism remains unknown. To study the mechanism, we investigated the effects of ethanol exposure on the beating rate of cultured chick cardiac myocytes. Primary cultures of cardiac myocytes were prepared from the ventricles of 14-day-old chick embryos and then treated with ethanol which, in the range of 0.3 to 1.5 vol%, increased the beating rate in a dose-dependent manner. Ethanol (0.6 vol%) caused an increase in the beating rate, but dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Certainly, in the calcium paradox, verapamil also has been reported to be ineffective (Alanen et al, 1984). In vitro, verapamil does not prevent the arrhythmia effect of alcohol in cultured cardiac myocytes either (Nakamura et al, 1999). When nifedipine is administered chronically to diabetic rats and the hearts are exposed to alcohol acutely (i.e., similar to our protocol for the chronic amlodipine treatments), this calcium channel blocker is able to attenuate the ethanol-induced reduction in peak tension developed (i.e., negative inotropic effect), contraction duration, and maximum velocity of tension development (Brown et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Certainly, in the calcium paradox, verapamil also has been reported to be ineffective (Alanen et al, 1984). In vitro, verapamil does not prevent the arrhythmia effect of alcohol in cultured cardiac myocytes either (Nakamura et al, 1999). When nifedipine is administered chronically to diabetic rats and the hearts are exposed to alcohol acutely (i.e., similar to our protocol for the chronic amlodipine treatments), this calcium channel blocker is able to attenuate the ethanol-induced reduction in peak tension developed (i.e., negative inotropic effect), contraction duration, and maximum velocity of tension development (Brown et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, no data is available on the electrophysiological effects of low alcohol exposure or on the exposure frequency. Clinically relevant concentrations of ethanol induced elevation of that was dependent on voltage-gated entry into the myocytes through I Ca,L (Brown et al, 1996 ; Solem et al, 2000 ) and reduction in the amplitude of K + currents of rats (Nakamura et al, 1999 ; Dopico, 2003 ; Liu et al, 2003 ). It was shown that the density of dihydropyridine binding sites were greater in cardiomycytes isolated from ethanol-consuming rats as compared to control groups (Brown et al, 1996 ).…”
Section: Low-dose Alcohol Beneficial Cardiovascular Effectsmentioning
confidence: 99%